1992
DOI: 10.1111/j.1432-1033.1992.tb16714.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and molecular dynamics simulation of calmodulin in the extended and in a bent conformation

Abstract: Analysis of sequence similarity and comparison of the three-dimensional (3D) structures of troponin C and calmodulin have revealed a sequence in the central helix of calmodulin with a high probability for bending. The three amino acids known to form a bend in the N-terminal portion of troponin C are also found in the central helix of calmodulin. The modelling of a bent calmodulin structure, using the dihedral angles of the three residues in the bend of troponin C as a 3D template, results in a conformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…This result indicates that: (a) the region of the pump involved in the dimerization and preserved after 7 h of denaturation at 44³C does not correspond to the CaM-binding domain and; (b) the association only occurs if at least the CaM-binding domain of one of the monomers has its native structure preserved. This last statement was con¢rmed by the progressive loss of energy transfer after the addition of increasing CaM concentrations to the native enzyme (Table 2), agreeing with Vorherr et al [8] who showed that CaM tends to maintain the enzyme in the monomeric state hindering its oligomerization.…”
Section: Mapping the Dimerization Domain Of The Pmcasupporting
confidence: 73%
See 4 more Smart Citations
“…This result indicates that: (a) the region of the pump involved in the dimerization and preserved after 7 h of denaturation at 44³C does not correspond to the CaM-binding domain and; (b) the association only occurs if at least the CaM-binding domain of one of the monomers has its native structure preserved. This last statement was con¢rmed by the progressive loss of energy transfer after the addition of increasing CaM concentrations to the native enzyme (Table 2), agreeing with Vorherr et al [8] who showed that CaM tends to maintain the enzyme in the monomeric state hindering its oligomerization.…”
Section: Mapping the Dimerization Domain Of The Pmcasupporting
confidence: 73%
“…On the other hand, it was demonstrated that the dimeric calcium pump is able to bind one CaM molecule [8]. In that paper, it was suggested that this result could be compatible with either the binding of the CaM molecule to only one monomer of the dimeric pump, or with its simultaneous binding to both monomers.…”
Section: Mapping the Dimerization Domain Of The Pmcamentioning
confidence: 63%
See 3 more Smart Citations